2020
DOI: 10.3390/genes12010026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Microhaplotype-Based Noninvasive Prenatal Test in Twin Gestations: Determination of Paternity, Zygosity, and Fetal Fraction

Abstract: As a novel type of genetic marker, the microhaplotype has shown promising potential in forensic research. In the present study, we analyzed maternal plasma cell-free DNA (cfDNA) samples from twin pregnancies to validate microhaplotype-based noninvasive prenatal testing (NIPT) for paternity, zygosity, and fetal fraction (FF). Paternity was determined with the combined use of the relMix package, zygosity was evaluated by examining the presence of informative loci with two fetal genome complements, and FF was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Research on FF in cases of multiple pregnancies remains limited (74). A large prospective, multicenter study demonstrated a FF range of 3-36% in twin pregnancies, with a mean FF of 12.2% (75).…”
Section: Fetal-placental Characteristicsmentioning
confidence: 99%
“…Research on FF in cases of multiple pregnancies remains limited (74). A large prospective, multicenter study demonstrated a FF range of 3-36% in twin pregnancies, with a mean FF of 12.2% (75).…”
Section: Fetal-placental Characteristicsmentioning
confidence: 99%
“…In addition, current research towards cffDNA detection is still in the exploratory stage. Preliminary shows that MPS combines microhaplotypes and mature SNPs and STR kit has certain application potential in NIPPT ( Bai et al, 2020 ; Ou and Qu 2020 ; Ou and Bai 2021 ; Shen et al, 2021 ). In this study, based on the CE platform, the 15 SNP-SNPs, provide a new and cost-effective strategy for NIPPT.…”
Section: Discussionmentioning
confidence: 99%
“…Another useful application of the MH methods is for detection of CNV anomalies in fetal DNA in Non-invasive prenatal testing (NIPT). MH methods are already in use for paternity testing (35)(36)(37)(38). For NIPT, panels can be designed to focus on genomic regions with the most likely copy number variation (e. g. chr 5, 13, 18, or 21) and the frequency of 3 rd MHs in targeted regions compared to the rest of the genome.…”
Section: Discussionmentioning
confidence: 99%